PENGARUH E-SERVICE QUALITY DAN E-TRUR TERHADAP SATISFITION PADA KANTOR BADAN PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU KABUPATEN WAKATOBI - Ahmad Ahmad; Nasrul Nasrul; Yusuf Yusuf (Pascasarjana Universitas Halu Oleo, 2023)
Public service providers are obliged to meet the standard components of services. This standard component of online public services is designed to provide the widest possible access to information to the public so that it is easier for the public to reach basic services that lead to community welfare. The main purpose of electronic services is people's satisfaction in using online services. This satisfaction can be realized if the services provided are in accordance with the established service standards or better than the service standards. This study aims to analyze the effect of e-service quality and e-trust on e-customer satisfaction. Determination of sample size using the slovin formula so that a sample of 76 respondents was obtained and the sample was drawn using the accidental random sampling method. Data analysis using Multivariate Regression with SPSS 24 software.Based on the results of the research conducted, it can be concluded that (1) E-service quality and e-trust secara simultan berpengaruh signifikan terhadap e-customer satisfaction at the office of investment and one door integrated services, wakatobi regency; (2) E-service quality berpengaruh positif dan signifikan terhadap e-customer satisfaction at the office of investment and one door integrated services, wakatobi regency; (3) E-trust berpengaruh positif dan signifikan terhadap e-customer satisfaction at the office of investment and one door integrated services, wakatobi regency.